Cell compensatory responses of fungi to damage of the cell wall induced by Calcofluor White and Congo Red with emphasis on Sporothrix schenckii and Sporothrix globosa. A review - Ortiz-Ramírez, Jorge A.; Cuéllar-Cruz, Mayra; López-Romero, Everardo (Frontiers in Cellular and Infection Microbiology, 2022)
The cell wall (CW) of fungi exhibits a complex structure and a characteristic chemical composition consisting almost entirely of interacting crystalline and amorphous polysaccharides. These are synthesized by a number of sugar polymerases and depolymerases encoded by a high proportion of the fungal genome (for instance, 20% in Saccharomyces cerevisiae). These enzymes act in an exquisitely coordinated process to assemble the tridimensional and the functional structure of the wall. Apart from playing a critical role in morphogenesis, cell protection, viability and pathogenesis, the CW represents a potential target for antifungals as most of its constituents do not exist in humans. Chitin, β-glucans and cellulose are the most frequent crystalline polymers found in the fungal CW. The hexosamine biosynthesis pathway (HBP) is critical for CW elaboration. Also known as the Leloir pathway, this pathway ends with the formation of UDP-N-GlcNAc after four enzymatic steps that start with fructose-6-phosphate and L-glutamine in a short deviation of glycolysis. This activated aminosugar is used for the synthesis of a large variety of biomacromolecules in a vast number of organisms including bacteria, fungi, insects, crustaceans and mammalian cells. The first reaction of the HBP is catalyzed by GlcN-6-P synthase (L-glutamine:D-fructose-6-phosphate amidotransferase; EC 2.6.1.16), a critical enzyme that has been considered as a potential target for antifungals. The enzyme regulates the amount of cell UDP-N-GlcNAc and in eukaryotes is feedback inhibited by the activated aminosugar and other factors. The native and recombinant forms of GlcN-6-P synthase has been purified and characterized from both prokaryotic and eukaryotic organisms and demonstrated its critical role in CW remodeling and morphogenesis after exposure of some fungi to agents that stress the cell surface by interacting with wall polymers. This review deals with some of the cell compensatory responses of fungi to wall damage induced by Congo Red and Calcofluor White.